Blood and faecal lead levels in children with various functional gastrointestinal disorders - Nergiz Sevinc; Namık Bilici; Eylem Sevinc; Erkan Dogan (Elsevier, 2022)
Introduction: To investigate the blood lead levels (BLLs) and faecal lead levels (FLLs) in children with various functional gastrointestinal disorders (FGIDs) and compare them with controls. Patients and methods: One hundred and two children with FGIDs defined by the Rome IV criteria, aged 4-18 years, and one hundred and two sex matched healthy children were enrolled in the study. Children with FGIDs were divided into three subgroups as functional constipation (FC) (n = 36), functional abdominal pain (FAP) (n = 36) and functional nausea (FN) (n = 30). The lead levels were measured using atomic absorption spectrometer. Results: The median BLLs in the FGIDs group was significantly higher than in controls (5.12 and 1.77 µg/dL, respectively). The BLLs were above 5 µg/dL in 51,9% of children with FGIDs. There was statistically significant difference in BLLs between FC subgroup and the other subgroups (FAP and FN) (p = 0.003, p < 0.001 respectively). The FLLs in the FGIDs group was significantly higher than in controls (28.08 and 0.01 µg/g, respectively). There was no significant difference in FLLs between FC subgroup and the other subgroups (p = 0.992, p = 0.989 respectively). No significant relation found between BLLs and FLLs of the FGIDs group (p = 0.123). Conclusion: This study revealed that children with FGIDs had higher BLLs and FLLs than controls and also more than half of children with FGIDs had BLLs ≥5 µg/dL which is considered as toxic level. These results might revive the question of whether or not clinicians need to evaluate routine BLLs in children with FGIDs. Resumen: Introducción: El objetivo del estudio fue determinar los niveles séricos y fecales de plomo en niños con distintos trastornos digestivos funcionales (TDF) en comparación con controles sanos. Pacientes y métodos: La muestra incluyó a 102 niños de 4-18 años con TDF definidos mediante los criterios de Roma IV y a 102 controles sanos emparejados por edad y sexo. Los niños con TDF se dividieron en 3 subgrupos: estreñimiento funcional (EF) (n = 36), dolor abdominal funcional (DAF) (n = 36) y náuseas funcionales (NF) (n = 30). Los niveles de plomo se midieron mediante espectrometría de absorción atómica. Resultados: El nivel de plomo en sangre (NPS) mediano fue significativamente mayor en niños con TDF en comparación con controles (5,12 vs. 1,77 µg/dl). Los NPS superaron los 5 µg/dl en el 51,9% del grupo TDF. Se observó una diferencia estadísticamente significativa en los NPS entre el subgrupo con EF y los otros dos subgrupos (DAF y NF) (p = 0,003 and p < 0,001, respectivamente). Los niveles de plomo en heces (NPH) fueron significativamente mayores en niños con TDF en comparación con controles (28,08 vs. 0,01 µg/g). No hubo diferencias significativas en los NPH entre el subgrupo de EF y los otros subgrupos (p = 0,992 y p = 0,989). No se encontró una correlación significativa entre los NPS y los NPH en niños con TDF (p = 0,123). Conclusión: El presente estudio demostró que los niveles séricos y fecales de plomo eran superiores en niños con TDF en comparación con controles, y que más de la mitad de los niños con TDF tenían NPS ≥ 5 µg/dl, que se consideran tóxicos. A la vista de estos resultados, cabe replantearse si los clínicos han de determinar los NPS de manera rutinaria en niños con TDF.